2011
DOI: 10.1186/1751-0147-53-60
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a dog elicits different cardiovascular and behavioral effects in pregnant and lactating goats

Abstract: BackgroundHeart rate and plasma cortisol concentration are often used in evaluation of physiological reactions to stress and fear, but arterial blood pressure is rarely measured in farm animals. Goats are prey animals and can be expected to react strongly to a predator, especially when they have kids. We hypothesized that exposure to a dog elicits a flight response during pregnancy and a fight response when goats have kids to defend. Arterial blood pressure and heart rate should increase in both these cases, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…We showed that the presence of the offspring and sucking by the offspring are important in attenuating HPA axis responses to isolation and restraint in lactating ewes [4] . The mechanisms by which the presence of the lambs, and suckling, influence the activity of the HPA axis are unknown, but at least part of the mechanism may involve oxytocin, which is released in response to cues from the infant, especially sucking [5] , [11] , [12] , [13] . There is experimental evidence that oxytocin can act centrally to attenuate the activity of the HPA axis [for review see [14] ], and we showed in the sheep that oxytocinergic neurons are located in close proximity to corticotrophin releasing hormone (CRH) and arginine vasopressin (AVP) neurons in the paraventricular nucleus (PVN) [4] .…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the presence of the offspring and sucking by the offspring are important in attenuating HPA axis responses to isolation and restraint in lactating ewes [4] . The mechanisms by which the presence of the lambs, and suckling, influence the activity of the HPA axis are unknown, but at least part of the mechanism may involve oxytocin, which is released in response to cues from the infant, especially sucking [5] , [11] , [12] , [13] . There is experimental evidence that oxytocin can act centrally to attenuate the activity of the HPA axis [for review see [14] ], and we showed in the sheep that oxytocinergic neurons are located in close proximity to corticotrophin releasing hormone (CRH) and arginine vasopressin (AVP) neurons in the paraventricular nucleus (PVN) [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In LK, an increase was measured in only half of the animals and the size of the increase was smaller. Baseline values and cortisol increases in response to an acute stressor (a dog) did not differ between pregnant and lactating goats (Olsson and Hydbring-Sandberg, 2011), indicating no general difference in HPA axis reactivity due to reproductive stage and supporting the interpretation that the smaller increase in cortisol in LK indeed reflects lower levels of stress during introduction.…”
Section: Discussionmentioning
confidence: 52%
“…At two weeks, the vocalization rate after dog bark in DAY-SEP and NON-SEP kids increased, while the SEP kids continued vocalising at a lower level. The sound of a dog bark has been shown to cause alertness in isolated goats [ 49 ] and exposure to a dog caused increased vocalization and elevated blood pressure and plasma cortisol in lactating goats [ 50 ]. Hence, the dog bark probably initiated an enhanced fear response in the arena test.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol concentration and heart rate are commonly used as physiological indicators of stress in goats [ 39 , 46 , 50 , 59 , 60 , 61 , 62 , 63 ]. Overall, concentrations of saliva cortisol were low in all samples, with large individual differences.…”
Section: Discussionmentioning
confidence: 99%